If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.23 + x = 5.47 Solving 1.23 + x = 5.47 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.23' to each side of the equation. 1.23 + -1.23 + x = 5.47 + -1.23 Combine like terms: 1.23 + -1.23 = 0.00 0.00 + x = 5.47 + -1.23 x = 5.47 + -1.23 Combine like terms: 5.47 + -1.23 = 4.24 x = 4.24 Simplifying x = 4.24
| -5x+7x=5x+9 | | 3y+5y+7y= | | 3x-2(x+1)-2=x-4 | | 2+5x+8-10=7y | | 2x+1-4=12 | | 1.23*x=5.47 | | 4+ln(x+1)=8 | | Y=20(0.25x)+180 | | (2O)+(4Z)=46 | | -3(2x-8)=-4(4x-1) | | 4+5x=4x+13 | | 2x+y=3-8 | | X+25+26+27=78 | | 3/2x9/2x-18 | | 100=8d | | -12-5(6-2m)=8 | | 87=4z+27 | | 11p-33=5p+5 | | 7-5y+2-1= | | 3+9+3x-1+5x+9x=96 | | x/5-15=x/4 | | -(5x-6)=4-7x | | 5.5=82.5k | | X+2+2=70 | | 5.5=82.5 | | 21t^2-18t+3=0 | | 21t^2-18t-3=0 | | 15m=56 | | 3(2x-5)=2(3x+1) | | -5x^2-60-20=0 | | (5x-6)^1/2=x | | -4.9t^2+8t+63=0 |